Determinants of the Intention to Purchase Organic Food Products among Portuguese Consumers - Santiago, Cesário Luís Nobre (2025)
The demand for organic food products has been increasing over the last few years in Portugal and worldwide because consuming these products benefits health and the environment. Also, its production values animal welfare and promotes economic development, improving the living conditions of rural communities in low population-density territories. Thus, the general objective of this research was to identify sustainable factors that impact the intention to purchase organic food products, allowing the production of knowledge about the attitudes, preferences, habits, and behaviors of Portuguese consumers about these types of products. To achieve this objective, a digital questionnaire was applied between January 9, 2024, and February 6, 2024, to collect the data. It was possible to select a sample of 413 consumers of Portuguese nationality, whose ages varied between 19 and 67 years old. The majority of respondents lived in urban communities (69.2%) of the Bragança (64.0%), Porto (10.4%), and Vila Real (5.1%) districts; had a positive nowledge level about organic food products (83.8%); and, recognized the European Union organic logo 68.0%). The most frequently consumed organic food products were fresh vegetables (62.7%) and fresh fruits 59.6%), which were usually purchased directly from the producer (50.5%). The results revealed that attitudes, environmental concerns, health awareness, and perceived price determine the intention to purchase organic food products. In addition to having a positive impact, these factors explained 57.5% of the variance of this variable, revealing that other equally important factors that were not considered in this study may impact the intention to purchase organic food products.